2008
DOI: 10.1111/j.1399-3054.2008.01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic tobacco plants overexpressing polyamine oxidase are not able to cope with oxidative burst generated by abiotic factors

Abstract: The molecular and biochemical mechanism(s) of polyamine (PA) action remain largely unknown. Transgenic tobacco plants overexpressing polyamine oxidase (PAO) from Zea mays exhibited dramatically increased expression levels of Mpao and high 1,3-diaminopropane (Dap) content. All fractions of spermidine and spermine decreased significantly in the transgenic lines. Although Dap was concomitantly generated with H(2)O(2) by PAO, the latter was below the detection limits. To show the mode(s) of H(2)O(2) scavenging, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
101
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 61 publications
10
101
1
Order By: Relevance
“…8) similarly to ZmPAO overexpression in the cell wall, suggesting that xylem differentiation and PCD induction are governed by a complex regulatory system in which intracellular PAs and apoplastic PAderived H 2 O 2 are likely integrated in coordinated signaling pathways; this is consistent with a previous hypothesis where salinity-induced cell death was proposed to be governed by the PAs/H 2 O 2 ratio (Moschou et al, 2008b). In this regard, Moschou et al (2008aMoschou et al ( , 2008b reported that the balance between the apoplastic PA catabolism versus the intracellular PA levels plays a central role in plant responses to salinity by governing the cell fate decision, leading to either induction of PCD or to tolerance mechanisms. Specifically, it was proposed that lowering the PA anabolism/PA catabolism ratio promotes PCD (S-ZmPAO and RNAi-SAMDC plants), while if PA anabolism predominates over catabolism, PCD fails to occur, allowing simultaneous induction of stress-responsive genes and plant tolerance (wild-type and A-ZmPAO plants).…”
Section: Discussionsupporting
confidence: 79%
“…8) similarly to ZmPAO overexpression in the cell wall, suggesting that xylem differentiation and PCD induction are governed by a complex regulatory system in which intracellular PAs and apoplastic PAderived H 2 O 2 are likely integrated in coordinated signaling pathways; this is consistent with a previous hypothesis where salinity-induced cell death was proposed to be governed by the PAs/H 2 O 2 ratio (Moschou et al, 2008b). In this regard, Moschou et al (2008aMoschou et al ( , 2008b reported that the balance between the apoplastic PA catabolism versus the intracellular PA levels plays a central role in plant responses to salinity by governing the cell fate decision, leading to either induction of PCD or to tolerance mechanisms. Specifically, it was proposed that lowering the PA anabolism/PA catabolism ratio promotes PCD (S-ZmPAO and RNAi-SAMDC plants), while if PA anabolism predominates over catabolism, PCD fails to occur, allowing simultaneous induction of stress-responsive genes and plant tolerance (wild-type and A-ZmPAO plants).…”
Section: Discussionsupporting
confidence: 79%
“…The apoplastic PAO from maize is best characterized enzyme, which oxidizes carbon at the endo-side of the N 4 -nitrogen of Spd and Spm using FAD as cofactor resulting into the formation of 4-aminobutanal, 1,3-diaminopropane (Dap), and H 2 O 2 and are thus considered to be involved in a terminal catabolic pathway (Fincato et al 2011). Another group of PAO resembles with mammalian PAOs, catalyzing a sequential retro conversion of Spm to Spd and Spd to Put with concomitant production of 3-aminopropanal and H 2 O 2 (Moschou et al 2008). Figure 1.…”
Section: Catabolismmentioning
confidence: 99%
“…DAO is Cu containing enzyme occur at high levels in dicots, particularly pea, chickpea, lentil, and soybean seedlings, loosely associated with cell wall. They catalyzes the oxidation of diamines like Put at the primary amino groups to generate 4-aminobutanal, H 2 O 2 and ammonia (NH 3 ) and the resulting aldehyde is further converted to g-aminobutyric acid (GABA) via D 1 -pyrroline (Moschou et al 2008). In contrast to DAO, PAO is FAD-dependent enzyme and occur at high levels in monocots which oxidizes only higher PAs like Spd and Spm (Sebela et al 2001) classified into families either by terminal oxidation or back conversion in apoplast and peroxisomes, respectively (Moschou et al 2008).…”
Section: Catabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…S-ZmPAO transgenic tobacco plants show increased inter-/intracellular levels of the reactive oxygen species (ROS) H 2 O 2 and O 2 .-and expression of antioxidant genes, which are nevertheless insufficient to scavenge these ROS efficiently (Moschou et al, 2008a(Moschou et al, , 2008b. The AS-ZmPAO tobacco young seedlings show tolerance to short-term salt stress, either due to increased PA content or decreased ROS levels from the impaired PA oxidation in the apoplast (Moschou et al, 2008a(Moschou et al, , 2008b.…”
Section: Introductionmentioning
confidence: 99%